2021
DOI: 10.1097/mnh.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

New insights into muscle function in chronic kidney disease and metabolic acidosis

Abstract: Purpose of review : Sarcopenia, defined as decreased muscle mass or function, is prevalent in chronic kidney disease (CKD) increasing the risk of mobility impairment and frailty. CKD leads to metabolic acidosis (MA) and retention of uremic toxins contributing to insulin resistance and impaired muscle mitochondrial energetics. Here we focus on the central role of muscle mitochondrial metabolism in muscle function. Recent findings : Mitochondrial dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…It has been shown that structural changes involving mitochondrial dynamics may result in mitochondrial dysfunction, thereby leading to CKD ( Chalupsky et al, 2021 ). Hence, the balance of mitochondrial dynamics is essential for skeletal muscle and myoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that structural changes involving mitochondrial dynamics may result in mitochondrial dysfunction, thereby leading to CKD ( Chalupsky et al, 2021 ). Hence, the balance of mitochondrial dynamics is essential for skeletal muscle and myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have reported that inflammation, oxidative stress and subsequent mitochondrial dysfunction are important processes in the maintenance of skeletal muscle function in CKD ( Watanabe et al, 2019 ; Chalupsky et al, 2021 ). The excessive accumulation of ROS has been proven to be an important link that leads to oxidative stress and mitochondrial dysfunction in CKD skeletal muscle atrophy ( Abrigo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those with sarcopenia were found to have a greater degree of metabolic acidosis. Metabolic acidosis induces insulin resistance, enhances mitochondrial stress, and activates multiple downstream cytokine mediators, leading to enhanced muscle catabolism [ 23 , 24 ]. Correction of metabolic acidosis was associated with better preservation of total muscle mass [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic events result in decreased cell growth and differentiation in skeletal muscle and consequently higher protein breakdown and lower synthesis. Inhibition of protein synthesis and stimulation of proteolysis contribute to impaired muscle function, muscle wasting, poor physical performance and decline in functional status [3,41 ▪▪ ,42 ▪ ,45,47,48 ▪ ,49–51].…”
Section: Clinical and Metabolic Risk Factors For Sarcopenia In Chroni...mentioning
confidence: 99%